2022
DOI: 10.3389/fphar.2022.927506
|View full text |Cite
|
Sign up to set email alerts
|

New insight into ischemic stroke: Circadian rhythm in post-stroke angiogenesis

Abstract: The circadian rhythm is an endogenous clock system that coordinates and optimizes various physiological and pathophysiological processes, which accord with the master and the peripheral clock. Increasing evidence indicates that endogenous circadian rhythm disruption is involved in the lesion volume and recovery of ischemic stroke. As a critical recovery mechanism in post-stroke, angiogenesis reestablishes the regional blood supply and enhances cognitive and behavioral abilities, which is mainly composed of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 189 publications
(217 reference statements)
0
10
0
Order By: Relevance
“…Promoting angiogenesis has been confirmed to be a critical recovery mechanism in ischemic stroke [ 29 ]. Recent studies have suggested that endothelial cells phenotypic processes could be regulated by brain and muscle Arnt-like 1 (Bmal1), the core circadian component [ 30 ], which promotes the proliferation, migration, and tube formation abilities of endothelial cells [ [31] , [32] , [33] ]. However, the expression of Bmal1 genes was lower in shift workers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promoting angiogenesis has been confirmed to be a critical recovery mechanism in ischemic stroke [ 29 ]. Recent studies have suggested that endothelial cells phenotypic processes could be regulated by brain and muscle Arnt-like 1 (Bmal1), the core circadian component [ 30 ], which promotes the proliferation, migration, and tube formation abilities of endothelial cells [ [31] , [32] , [33] ]. However, the expression of Bmal1 genes was lower in shift workers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of symptoms such as neurological dysfunction is induced. [14] Studies have shown that multiple pathways of injury in the ischemic cascade are simultaneous and interact with each other; therefore, combined therapy targeting several pathways of ischemic injury may have advantages over single pathway strategies. [15] Free radicals are the main cause of ischemic cerebrovascular injury, and the massive production of free radicals after brain tissue injury promotes secondary brain tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…A series of symptoms such as neurological dysfunction is induced. [14] Studies have shown that multiple pathways of injury in the ischemic cascade are simultaneous and interact with each other; therefore, combined therapy targeting several pathways of ischemic injury may have advantages over single pathway strategies. [15]…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is an important factor for post-stroke recovery, and it is tightly related to the activation and functioning of glial cells [ 136 ]. Clock genes (in particular, Cry1/2 ) are involved in the regulation of different stages of the angiogenesis process [ 137 , 138 ].…”
Section: Circadian System and Post-stroke Recoverymentioning
confidence: 99%